Pengaruh Penggunaan Media Pembelajaran Film Animasi Terhadap Hasil Belajar Siswa di Kelas IV SDI Bertingkat Labuang Baji - St. Asdianti; Khaeruddin Khaeruddin; Hilmi Hambali (Universitas Negeri Makassar, 2022)
Abstract. The main problem in this study is the influence of animated film media on student learning outcomes in grade IV SDI Labuang Baji Level. This study aims to determine the effect of using animated film media on student learning outcomes in grade IV SDI Labuang Baji Level. This type of research is quantitative or experimental research (Pre-experimental design) with a quasi-experimental form with a nonequivalent control group design. The sample and population are fourth grade students of SDI Labuang Baji, Mamajang District, Makassar City, totaling 50 students. The instruments used to collect data are interviews and tests. The results showed that the data were analyzed using descriptive analysis and inferential analysis. For inferential analysis using the t-test formula, it is known that the tcount obtained from the experimental class is -18,485 and the tcount obtained from the control class is -13,854 with both classes having a frequency of df = 25-2=23, at a significant level = 0.05 or 5% obtained t table is 2.068. So tcount > ttable or -18,485 > 2,068 this indicates that H0 is rejected and H1 is accepted. Based on the results of these studies, it can be concluded that there is an influence of animated film learning media on student learning outcomes on animal life cycle material in grade IV SDI Labuang Baji Level. Keywords: Influence, Learning Media, Animated Film